Strategies for enhancing the perylene diimide photocatalytic degradation activity: method, effect factor, and mechanism. Issue 3 (1st March 2021) - Zhou, Chengyun; Xia, Wu; Huang, Danlian; Cheng, Min; Zhang, Hanjie; Cai, Tao; Xiong, Weiping; Yang, Yang; Song, Biao; Wang, Wenjun; Zhou, Man; Zeng, Guangming
Abstract : Strategies to improve the photocatalytic activity of PDI are summarized. The system factor and water chemistry affecting the photocatalytic activity for organic pollutant removal are discussed. The stability and future challenges are discussed. Abstract : In the past few decades, countless organic and inorganic pollutants caused serious environmental problems all over the world. One way to remove or degrade pollutants in the environment is to use oxidizing agents. Photocatalytic technology uses unlimited solar energy to efficiently oxidize and remove organic pollutants. Recently, perylene diimide (PDI)-based nanomaterials have been widely used in photocatalytic degradation. However, there are no reviews on the use of PDI-based composites to remove organic pollutants from contaminated water. Therefore, a review paper is needed to fully understand the current status and prospects of this field. The main purpose of this work is to highlight the recent progress of PDI-based photocatalysts in the removal of organic pollutants. In this review, the basic molecular design and properties of PDI molecules are first described. Then, strategies to improve the photocatalytic activity of PDI are summarized. The system factor and water chemistry affecting the photocatalytic activity for organic pollutant removal are also discussed. Lastly, the stability and future challenges of PDI-based composites are briefly discussed.